2013
DOI: 10.4103/0028-3886.121912
|View full text |Cite
|
Sign up to set email alerts
|

HIV neuropathy in pre-HAART patients and it′s correlation with risk factors in Central India

Abstract: HIV-SN is more common among pre-HAART patients with low level of hemoglobin, serum albumin, BMI, and CD4 T-cell count. Hence, it is found that neuropathy can be prevented by improving immune as well as nutritional status of HIV infected patients. So, BPNS, being a simple diagnostic tool should therefore be routinely applied to screen the neuropathy, to minimize the negative impact it has on the quality of life in patients with HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
(25 reference statements)
0
4
1
Order By: Relevance
“…In our study, there was no association between gender and PN and is similar to previous studies. [ 23 , 24 ] Likewise, we did not find an association with SSW-EMLA test in detecting PN in our study, although other studies have shown the incidence of HIV PN was associated with increased age. [ 4 ] This is likely related to the poor immunological status found in our patients as shown in lower CD4+ finding.…”
Section: Discussioncontrasting
confidence: 75%
“…In our study, there was no association between gender and PN and is similar to previous studies. [ 23 , 24 ] Likewise, we did not find an association with SSW-EMLA test in detecting PN in our study, although other studies have shown the incidence of HIV PN was associated with increased age. [ 4 ] This is likely related to the poor immunological status found in our patients as shown in lower CD4+ finding.…”
Section: Discussioncontrasting
confidence: 75%
“…The participants in whom the ARV regimen was not changed were also likely to improve. This is possible because it is either that the PN was not severe, the PN had just started or it was not suspected to be augmented with a particular toxic ARV type (Dubey et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In an Indian study on 75 patients, 40% had clinical HIV-associated sensory neuropathy (HIV-SN). [ 49 ] HIV-SN considerably affects their quality of life. Symptomatic relief therapy is usually not satisfactory.…”
Section: N Europathy D Ue To I mentioning
confidence: 99%
“…[ 54 ] According to a Western study, two-thirds of HIV-SN is subclinical,[ 55 ] which was less common (around 16%) in Indian study. [ 49 ]…”
Section: N Europathy D Ue To I mentioning
confidence: 99%